Sikap Petani terhadap Pengembangan Agrowisata Subak Anggabaya, Kecamatan Denpasar Timur, Kota Denpasar - PRADNYAYONI, I GUSTI AYU AGUNG; WINDIA, I WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Farmers Attitudes Towards The Development of Agro-Tourism in Subak Anggabaya, Denpasar Timur District, Denpasar City.  The members of subak as an irrigation management must play an active role in the development of agro-tourism in order to create agro-tourism that is feasible in terms of attractions, accessibility, amenities, and ancillaries. The purpose of this study is to examine the development of agro-tourism and analyze the attitudes of farmers towards the development of agro-tourism in Subak Anggabaya, East Denpasar. The data collection process went through four stages, namely structured interviews, in-depth interviews, observation, and documentation. Respondents in this study amounted to 53 people. This study uses a qualitative descriptive analysis method. The results indicate the condition of the Subak Anggabaya area already supports several requirements for agro-tourism development. Subak Anggabaya agrotourism is classified as very good in terms of attractions and accessibility, but is still classified as lacking in aspects of amenities and institutions. Other results show that Subak Anggabaya’s members agree on the development of agro-tourism in Subak Anggabaya by achieving a score of 4.11. There are several components of tourism development that need to be developed in Subak Anggabaya agro-tourism. Although the farmers showed agreement, some farmers did not know what agro-tourism is. Intensive socialization is needed by the government regarding the development of agro-tourism.